2010
DOI: 10.1021/nn101719r
|View full text |Cite
|
Sign up to set email alerts
|

Field Electron Emission Characteristics and Physical Mechanism of Individual Single-Layer Graphene

Abstract: Due to its difficulty, experimental measurement of field emission from a single-layer graphene has not been reported, although field emission from a two-dimensional (2D) regime has been an attractive topic. The open surface and sharp edge of graphene are beneficial for field electron emission. A 2D geometrical effect, such as massless Dirac fermion, can lead to new mechanisms in field emission. Here, we report our findings from in situ field electron emission characterization on an individual singe-layer graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
105
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 11 publications
7
105
0
Order By: Relevance
“…[5,6] Several groups have demonstrated that graphene does show promising CFE properties such as a low emission threshold field and large emission current density. [7][8][9][10][11][12][13] What we will show in this paper is that the unique electronic properties of graphene and its monolayer atomic structure result in a novel electron line source with coherent field emission that can produce interference patterns of extended objects with linear sizes comparable to the length of the graphene edge. What makes graphene unique is that its two-dimensional electron system is well described by a superposition of 2p carbon orbitals and that its low energy excitations behave like Dirac particles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] Several groups have demonstrated that graphene does show promising CFE properties such as a low emission threshold field and large emission current density. [7][8][9][10][11][12][13] What we will show in this paper is that the unique electronic properties of graphene and its monolayer atomic structure result in a novel electron line source with coherent field emission that can produce interference patterns of extended objects with linear sizes comparable to the length of the graphene edge. What makes graphene unique is that its two-dimensional electron system is well described by a superposition of 2p carbon orbitals and that its low energy excitations behave like Dirac particles.…”
mentioning
confidence: 99%
“…The unusual up bending Fowler-Nordmeim plot (the inset of Fig.3) in the regime of weak fields and/or short graphene height has been confirmed by another experiment. [13] …”
mentioning
confidence: 99%
“…They possess fascinating electrical and mechanical properties and have promising prospects in many applications such as field-effect transistors [2,3], photo detectors [4], supercapacitors [5,6], Li ion batteries [7,8], memory devices [9], and so on. Graphene is also an excellent field emission (FE) material due to its atomic thin edge which leads to a large field enhancement factor [10][11][12][13]. In comparison with one-dimensional FE materials such as carbon nanotubes (CNTs), which have nanosharp tips and excellent electrical conductivity and their superior FE performance has been well reported in recent years [14−16], graphenes have advantages in longtime stable FE.…”
Section: Introductionmentioning
confidence: 99%
“…The ion incidence angle was normal to the surface, and irradiations were performed at room temperature for 10 s. The basal and working pressures of the ion beam chamber were ~10 -4 and 5 × 10 -2 Pa, respectively. The ion dose for 10 s irradiation was observed to be 1.75 × 10 16 ions/cm 2 . The energy and beam diameter of Ne + ions were 600 eV and 4 cm, respectively.…”
mentioning
confidence: 96%
“…CNTs are very effective for FEDs due to their sharp emission tips and high aspect ratio [8][9][10][11]. Materials such as conical nanocarbon structures (CNCSs) [12], graphene [13][14][15][16], and zinc oxide (ZnO) based nanostructures [17][18][19][20] Recently, carbon based transparent and flexible FEE of graphene with multi-wall carbon nanotubes (MWNTs) have been reported [27]. In our recent reports, we used a very straightforward method of the random networks of single-walled carbon nanotubes (SWCNTs) on flat polymer substrates to fabricate transparent and flexible FEE [28].…”
mentioning
confidence: 99%